Four childhood atopic dermatitis subtypes identified from trajectory and severity of disease and internally validated in a large UK birth cohort. (9th May 2021) - Mulick, A.R.; Mansfield, K.E.; Silverwood, R.J.; Budu‐Aggrey, A.; Roberts, A.; Custovic, A.; Pearce, N.; Irvine, A.D.; Smeeth, L.; Abuabara, K.; Langan, S.M.
Summary: Background: Atopic dermatitis (AD) disease activity and severity is highly variable during childhood. Early attempts to identify subtypes based on disease trajectory have assessed AD presence over time without incorporating severity. Objectives: To identify childhood AD subtypes from symptom severity and trajectories, and determine associations with genetic risk factors, comorbidities and demographic and environmental variables. Methods: We split data from children in the Avon Longitudinal Study of Parents and Children birth cohort into development and validation sets. To identify subtypes, we ran latent class analyses in the development set on AD symptom reports up to age 14 years. We regressed identified subtypes on nongenetic variables in mutually adjusted, multiply imputed (genetic: unadjusted, complete case) multinomial regression analyses. We repeated analyses in the validation set and report confirmed results. Results: There were 11 866 children who contributed to analyses. We identified one Unaffected/Rare class (66% of children) and four AD subtypes: Severe–Frequent (4%), Moderate–Frequent (7%), Moderate–Declining (11%) and Mild–Intermittent (12%). Symptom patterns within the first two subtypes appeared more homogeneous than the last two. Filaggrin ( FLG ) null mutations, an AD polygenic risk score (PRS), being female, parental AD and comorbid asthma were associated with higher risk for some or all subtypes; FLG, AD‐PRS and asthma associations were stronger along a subtype gradient arranged by increasing severity and frequency; FLG and AD‐PRS further differentiated some phenotypes from each other. Conclusions: Considering severity and AD trajectories leads to four well‐defined and recognizable subtypes. The differential associations of risk factors among and between subtypes is novel and requires further research. Abstract : What's already known about this topic? Atopic dermatitis (AD) is a heterogeneous condition in terms of both disease activity and severity. Childhood AD phenotypes in previous studies have focused only on disease activity. What does this study add? We incorporate disease severity over time to derive four clinically recognizable AD phenotypes using data‐driven methods. Disease severity improved over time in all phenotypes (even in those with high probability of activity in late childhood and adolescence). Several established risk factors, including genetic associates, were associated with our proposed phenotypes, with most factors more strongly associated with phenotypes reporting the worst symptoms. Fewer factors differentiated between more Frequent and Declining/Intermittent phenotypes. Linked Comment: C. Vestergaard. Br J Dermatol 2021; 185:477 .